2021
DOI: 10.3390/biom11030468
|View full text |Cite
|
Sign up to set email alerts
|

Cerrena unicolor Laccases, Genes Expression and Regulation of Activity

Abstract: A white rot fungus Cerrena unicolor has been identified as an important source of laccase, unfortunately regulation of this enzyme genes expression is poorly understood. Using 1D and 2D PAGE and LC-MS/MS, laccase isoenzymes were investigated in the liquid filtrate of C. unicolor culture. The level of expression of laccase genes was measured using qPCR. The elevated concentrations of copper and manganese in the medium caused greatest change in genes expression and three laccase transcripts were significantly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…5A , laccase activity decreased as the concentration of additive GSH increased, suggesting a dose-dependent negative regulation of laccase production by GSH. Previous studies have explored the effects of phenolic compounds (such as ferulic acid and veratric acid) and metal ions (such as Cu 2+ , Mn 2+ , and Cd 2+ ) on fungal laccase production ( 23 , 48 50 ). This is the first evidence demonstrating the inhibitory effect of oligopeptide GSH on fungal laccase activity.…”
Section: Resultsmentioning
confidence: 99%
“…5A , laccase activity decreased as the concentration of additive GSH increased, suggesting a dose-dependent negative regulation of laccase production by GSH. Previous studies have explored the effects of phenolic compounds (such as ferulic acid and veratric acid) and metal ions (such as Cu 2+ , Mn 2+ , and Cd 2+ ) on fungal laccase production ( 23 , 48 50 ). This is the first evidence demonstrating the inhibitory effect of oligopeptide GSH on fungal laccase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the high-efficient absorption, accumulation and utilization of Cu could be one of the reasons for the good laccase expression induced by GHK-Cu. In fact, the promoter region of laccase gene may contain elements responding to Cu 2+ regulation, which regulated laccase gene expression in a strain-dependent manner ( Degerli et al, 2019 ; Pawlik et al, 2021 ). It has been proved that the increase in laccase gene expression level contributed to the increase in laccase production ( Rodrigues et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had indicated excellent laccase secretion ability of Cerrena unicolor (Jamroz et al 2004;Rola et al 2013;Kachlishvili et al 2014Kachlishvili et al , 2021Pawlik et al 2021;Zhang et al 2021). There are also many studies on the effect of lignocellulose materials on laccase activity from C. unicolor.…”
Section: Effect Of Nutrient Medium On Laccase Activity Secreted By Ce...mentioning
confidence: 94%